PENGARUH KEPUASAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TAPANULI TENGAH - Jumika Soupiawati Simbolon; Mansur Tanjung; Kaharuddin Kaharuddin (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to determine whether or not there is an influence of job satisfaction and career development on employee performance at the Population and Civil Registration Office of Central Tapanuli Regency. The type of research used in this study is a quantitative research method with a descriptive approach. The sample in this study were employees at the Population and Civil Registration Office of Central Tapanuli Regency with a questionnaire distribution of 77 (seventy seven) respondents. The results of the study showed that based on the Determination Coefficient Analysis obtained of 0.606, this means that what happened to the variation of the dependent variable Performance 60.6% was determined by the independent variables Job Satisfaction and Career Development simultaneously and the remaining 30.4% was determined by other factors not discussed in this study such as Division of Labor, Supervision, Leadership, Competence, Motivation, Communication, and so on. From the results of the t-test in the study, it is known that the calculated t value of Job Satisfaction is 4.919> t table 1.99254, with a significance of 0.001 <0.05 and Career Development is 2.761> t table 1.99254 with a significance of 0.007 <0.05, then the hypothesis stating that Job Satisfaction has a Positive and Significant effect on Employee Performance at the Population and Civil Registration Service of Central Tapanuli Regency can be accepted, and Career Development has a Positive and Significant effect on Employee Performance at the Population and Civil Registration Service of Central Tapanuli Regency can be accepted. Meanwhile, from the results of the F test, it is known that the calculated F value is 56,900> F table 3.12 and the significance of the calculated F is 0.001 <0.05 so that the hypothesis stating that Supervision and Division of Work have a Positive and Significant Effect on the Effectiveness of Employee Work at the Population and Civil Registration Service of Central Tapanuli Regency can be accepted. Keywords: Job Satisfaction, Career Development and Performance Abstrak. Penelitian ini bertujuan untuk mengetahui Ada Tidaknya Pengaruh Kepuasan Kerja Dan Pengembangan Karir Terhadap Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Tapanuli Tengah. Jenis penelitian yang digunakan dalam penelitian ini adalah metode penelitian kuantitatif dengan pendekatan deskriptif. Sampel dalam penelitian ini adalah pegawai yang ada pada Dinas Kependudukan dan Catatan Sipil Kabupaten Tapanuli Tengah dengan penyebaran kuesioner berjumlah 77 (Tujuh puluh tujuh) responden. Hasil penelitian diketahui bahwa berdasarkan Analisis Koefisien Determinasi yang diperoleh sebesar 0,606 hal ini berarti bahwa yang terjadi pada variasi variabel terikat Kinerja 60,6% ditentukan oleh variabel bebas Kepuasan Kerja dan Pengembangan Karir secara serempak dan sisanya sebesar 30,4 % ditentukan oleh faktor lain yang tidak dibahas dalam penelitian ini seperti Pengembangan Karir, Kepuasan Kerja, Kepemimpinan, Kompetensi, Motivasi, Komunikasi, dan lain sebagainya. Dari Hasil uji t pada penelitian diketahui bahwa nilai t hitung Kepuasan Kerja sebesar 4.919 > t tabel 1.99254, dengan signifikan 0,001 < 0,05 dan Pengembangan Karir sebesar 2.761 > t tabel 1.99254 dengan signifikan 0,007 < 0,05, maka hipotesis yang menyatakan Kepuasan Kerja berpengaruh Positif dan Signifikan terhadap Kinerja Pegawai pada Dinas Kependudukan dan Catatan Sipil Kabupaten Tapanuli Tengah dapat diterima, dan Pengembangan Karir berpengaruh Positif dan Signifikan terhadap Kinerja Pegawai pada Dinas Kependudukan dan Catatan Sipil Kabupaten Tapanuli Tengah dapat diterima. Sedangkan dari hasil uji F diketahui Nilai F hitung 56.900 > F tabel 3.12 dan signifikasi F hitung 0.001 < 0,05 sehingga hipotesis yang menyatakan Kepuasan Kerja dan Pengembangan Karir berpengaruh Positif dan Signifikan terhadap Kinerja Pegawai pada Dinas Kependudukan dan Catatan Sipil Kabupaten Tapanuli Tengah dapat diterima. Kata Kunci: Kepuasan Kerja, Pengembangan Karir dan Kinerja